2021
DOI: 10.1007/s00535-020-01746-z
|View full text |Cite|
|
Sign up to set email alerts
|

Evidence-based clinical practice guidelines for irritable bowel syndrome 2020

Abstract: Managing irritable bowel syndrome (IBS) has attracted international attention because single-agent therapy rarely relieves bothersome symptoms for all patients. The Japanese Society of Gastroenterology (JSGE) published the first edition of evidence-based clinical practice guidelines for IBS in 2015. Much more evidence has accumulated since then, and new pharmacological agents and non-pharmacological methods have been developed. Here, we report the second edition of the JSGE-IBS guidelines comprising 41 questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
84
1
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 105 publications
(101 citation statements)
references
References 227 publications
3
84
1
13
Order By: Relevance
“…A narrative review of meta-analyses published in March 2020 [ 110 ] found that four out of five meta-analyses suggested that fibre supplementation could provide significant clinical improvement via the Global Assessment of IBS Symptoms evaluation. This is also reflected in the recent Japanese IBS treatment guidelines suggesting bulking polymers or dietary fibre as an effective IBS treatment ranked as Level A evidence—strong recommendation [ 111 ], although no specific amount was specified.…”
Section: Discussionmentioning
confidence: 99%
“…A narrative review of meta-analyses published in March 2020 [ 110 ] found that four out of five meta-analyses suggested that fibre supplementation could provide significant clinical improvement via the Global Assessment of IBS Symptoms evaluation. This is also reflected in the recent Japanese IBS treatment guidelines suggesting bulking polymers or dietary fibre as an effective IBS treatment ranked as Level A evidence—strong recommendation [ 111 ], although no specific amount was specified.…”
Section: Discussionmentioning
confidence: 99%
“…5-HT 3 receptors in the gastrointestinal tract modulate physiological responses such as gastric emptying, colonic peristalsis and transit [ 111 , 112 , 113 ]. Thus, 5-HT 3 receptor antagonists are used to treat diarrhea predominant irritable bowel syndrome [ 22 , 114 , 115 ] in addition to chemotherapy-induced nausea and vomiting (CINV) or post-operative vomiting (POV) [ 30 , 116 , 117 ]. Genetic polymorphisms in genes for 5-HT 3 B, 5-HT 3 C, and 5-HT 3 D, predominantly expressed in the gastrointestinal tract and various brain regions [ 13 , 14 ], may contribute to facilitating individual risk predictions ( Table 1 ).…”
Section: Distribution Of 5-ht 3 Receptorsmentioning
confidence: 99%
“…), all of which, are related to abnormalities in the functional relationship between the brain and intestine (brain-gut connection). Since IBS is a gastrointestinal psychosomatic disorder that often develops and worsens with stress, it is important to treat it from both the physical and mental aspects [ 4 ]. We shall review recent research on cognitive-behavioral therapy—one of the most widely studied psychological treatments for IBS.…”
Section: Introductionmentioning
confidence: 99%